THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT, INTERNAL MARKETING AND ORGANIZATIONAL COMMITMENT ON TURNOVER INTENTION: A Case of Wisma Bahasa, Indonesia - Febby Meilisa; Innocentius Bernarto (Kusuma Negara Business School, 2020)
This research attempts to identify and measure the effect of perceived organizational support and internal marketing on turnover intention with organizational commitment as moderating factor in BIPA institution through quantitative approach: PLS-SEM and path analysis. Questionnaire is used to collect data of independent variables and data collected is analyzed using SMARTPLS 3.0 program. Population of the study is taken from instructors of Wisma Bahasa. Based in Yogyakarta, areas of operation of the institution include Yogyakarta itself, Jakarta, Papua and recently Bali. Data collection is conducted through the use of digital questionnaire Google Form distributed to 48 subjects. Statistical analysis using PLS-SEM employs Path Analysis method comprising of 2 phases, namely outer model and inner model. Outer model consists of validity and reliability testing, and inner model focuses on hypothesis testing. The result of the study shows that while Perceived Organizational Support and Organizational Commitment affects Turnover Intention negatively, or in other words suppresive the intention, Internal Marketing does not. In the case of Wisma Bahasa, it appears that Turnover Intention remains to exist despite the institutions effort to promote Internal Marketing.